Predictors of in-hospital mortality in patients with ST-segment elevation myocardial infarction undergoing pharmacoinvasive treatment - Felipe Jose de Andrade Falcao; Claudia Maria Rodrigues Alves; Adriano Henrique Pereira Barbosa; Adriano Caixeta; Jose Marconi Almeida Sousa; Jose Augusto Marcondes Souza; Amaury Amaral; Luiz Carlos Wilke; Fatima Cristina A. Perez; Iran Goncalves Junior; Edson Stefanini; Antonio Carlos Carvalho (Clinics, 2013)
OBJECTIVES: To identify predictors of in-hospital mortality in patients with acute myocardial infarction undergoing pharmacoinvasive treatment. METHODS: This was an observational, prospective study that included 398 patients admitted to a tertiary center for percutaneous coronary intervention within 3 to 24 hours after thrombolysis with tenecteplase. ClinicalTrials.gov: NCT01791764 RESULTS: The overall in-hospital mortality rate was 5.8%. Compared with patients who survived, patients who died were more likely to be older, have higher rates of diabetes and chronic renal failure, have a lower left ventricular ejection fraction, and demonstrate more evidence of heart failure (Killip class III or IV). Patients who died had significantly lower rates of successful thrombolysis (39% vs. 68%; p = 0.005) and final myocardial blush grade 3 (13.0% vs. 61.9%; p<0.0001). Based on the multivariate analysis, the Global Registry of Acute Coronary Events score (odds ratio 1.05, 95% confidence interval (CI) 1.02-1.09; p = 0.001), left ventricular ejection fraction (odds ratio 0.9, 95% CI 0.89-0.97; p = 0.001), and final myocardial blush grade of 0-2 (odds ratio 8.85, 95% CI 1.34-58.57; p = 0.02) were independent predictors of mortality. CONCLUSIONS: In this prospective study that evaluated patients with ST-segment elevation myocardial infarction treated by a pharmacoinvasive strategy, the in-hospital mortality rate was 5.8%. The Global Registry of Acute Coronary Events score, left ventricular ejection fraction, and myocardial blush were independent predictors of mortality in this high-risk group of acute coronary syndrome patients.